Gene regulation and signaling pathways in immune response to respiratory sensitizers: a database analysis - Jefferis, Taylor; Liu, James Y.; Griffin, Kiera L.; Gibb, Matthew; Sayes, Christie M. (Frontiers in Immunology, 2025)
IntroductionHumans are regularly exposed to environmental substances through inhaled air. Some chemicals or particles are respiratory sensitizers that can cause adverse respiratory health effects by triggering amplified immune responses. Understanding the process of respiratory sensitization and identifying potential sensitizers have been challenging due to the complexity of the underlying mechanisms.MethodsThis study leverages the transcriptomics from a previous in vitro 3D human lung model to investigate the pathways of chemical respiratory sensitization. Differentially expressed genes between two known and two nonsensitizers are cross-referenced against databases on biological processes and disease pathways.ResultsThe GO results revealed 43 upregulated genes, and the KEGG revealed 52. However, only 18 upregulated genes were common between GO and KEGG. The GO results revealed 26 downregulated genes, and the KEGG revealed 40. However, only 9 of those downregulated genes were common.DiscussionThese findings support using multiple databases in perturbed gene analyses. The results from this study and data available in the scientific literature contribute toward building a biomarker profile for identifying respiratory sensitizers.